Holocaust remembrance between the national and the transnational : the Stockholm International Forum and the first decade of the International Task Force - Allwork, Larissa (Bloomsbury Academic, 2015)
Money ought not to be the last memory of the Holocaust: the international and transnational historical context for the Stockholm International Forum -- Connecting with the world? The international task force and the organization and media reception of the Stockholm International Forum -- The global legacies of the Stockholm International Forum (2000): The subsequent Stockholm conferences and the International Task Force (2000-2008) -- Holocaust remembrance between the national and transnational: the International Task Force British/Lithuanian "liaison project" -- Interpreting the SIF 2000: the limits of the "new cosmopolitan" global theory